Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/apt.15102
|View full text |Cite
|
Sign up to set email alerts
|

Sustained virological response to hepatitis C treatment decreases the incidence of complications associated with type 2 diabetes

Abstract: Background:The role of hepatitis C (HCV) eradication on the long-term complications of type 2 diabetes mellitus remains incompletely studied.Aim: To investigate whether antiviral treatment impacted risk of acute coronary syndrome, end-stage renal disease, ischaemic stroke, and retinopathy among diabetic patients from the four US health systems comprising the Chronic Hepatitis Cohort Study (CHeCS). Methods:We included CHeCS HCV patients with diagnosis codes for type 2 diabetes who were on antidiabetic medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…HCV anti‐viral therapy with attainment of sustained virological response (SVR), which is virological cure, has hepatic benefits, such as normalising liver enzymes, halting the progression of liver disease and reducing the risk of hepatocellular carcinoma. Studies in the interferon‐based treatment era showed that SVR was also associated with a reduced risk of mixed cryoglobulinaemia; glomerulonephritis; porphyria cutanea tarda; NHL; and, possibly, diabetes mellitus …”
Section: Introductionmentioning
confidence: 99%
“…HCV anti‐viral therapy with attainment of sustained virological response (SVR), which is virological cure, has hepatic benefits, such as normalising liver enzymes, halting the progression of liver disease and reducing the risk of hepatocellular carcinoma. Studies in the interferon‐based treatment era showed that SVR was also associated with a reduced risk of mixed cryoglobulinaemia; glomerulonephritis; porphyria cutanea tarda; NHL; and, possibly, diabetes mellitus …”
Section: Introductionmentioning
confidence: 99%
“…Of the 55 papers published in 2015, six (11%) included time‐varying covariates in Fine‐Gray subdistribution hazard model . Of the 102 papers published in the first 5 months of 2019, five (5%) included time‐varying covariates in the Fine‐Gray subdistribution hazard model . These 11 papers are summarized in Table .…”
Section: Literature Review Of the Use Of Time‐varying Covariates Withmentioning
confidence: 99%
“…Of the 11 studies that incorporated time‐varying covariates, six (55%) provided, in at least one instance, an interpretation that suggested that the time‐varying covariate was associated with the risk of the event . As risk has a distinct probabilistic interpretation, it appears that these authors were suggesting that the time‐varying covariate was associated with the CIF.…”
Section: Literature Review Of the Use Of Time‐varying Covariates Withmentioning
confidence: 99%
“…4 It is clear from available research outcomes that HCV infection has a clear association with increased risk of T2D prevalence across various populations. [1][2][3][4] A cross-sectional study from Saudi Arabia (N = 300), investigating the association between the two conditions finds 8% and 2% respective prevalence of HCV among T2D and nondiabetics. 5 Multivariate regression analysis for the prevalence outcomes defines an increased prevalence of HCV infection in T2D patients.…”
mentioning
confidence: 99%